2015
DOI: 10.1080/19338244.2015.1058237
|View full text |Cite
|
Sign up to set email alerts
|

Health perception and healthy lifestyle behaviors of female factory workers

Abstract: This study aims at the assessment of heath perception and healthy lifestyle behaviors of female workers at a food industry factory. Sociodemographic characteristics, a questionnaire form encompassing health-related characteristics, and Healthy Lifestyle Behaviors (HLSB) Scale II are utilized for data collection. The percentage of smokers is determined to be 20.9% among the workers and about 35.6% of them are considered as slightly overweight or overweight, based on their body mass index values. About 81.7% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
2
6
0
1
Order By: Relevance
“…In the current study, the workers had the highest score for spiritual development followed by interpersonal relationships, health responsibility, nutrition, stress management and physical activity, which is consistent with the findings reported by Küçük 16. In other words, spiritual development is the healthy lifestyle behavior most contributing to health promotion among the workers 16,18.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the current study, the workers had the highest score for spiritual development followed by interpersonal relationships, health responsibility, nutrition, stress management and physical activity, which is consistent with the findings reported by Küçük 16. In other words, spiritual development is the healthy lifestyle behavior most contributing to health promotion among the workers 16,18.…”
Section: Discussionsupporting
confidence: 90%
“…In other words, spiritual development is the healthy lifestyle behavior most contributing to health promotion among the workers 16,18. The finding of high scores for spiritual development can be attributed to culture and place of living.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study initiated by the World Bank also concludes that for China, more than 50% of the disease burden increase due to chronic diseases can be controlled by adjusting health‐risk behaviors . At present, many studies on health behaviors conducted in academia, involving women, adolescents, college students, elderly people, and corresponding factors, have further confirmed the importance of health behaviors to individual health and laid the foundation for the development of this study.…”
Section: Introductionmentioning
confidence: 54%
“…In the Europe region of World Health Organization (WHO), more than 50% of men and women are overweight, and 23% of the women and 20% of the men are obese [4]. In a study conducted on female factory workers, it is found that 35.6% of the workers are overweight or obese [5]. The increase in the risk factors increases the prevalence of the chronic diseases and makes it difficult to control these diseases.…”
Section: Introductionmentioning
confidence: 99%